A Roadmap for Participatory Chestnut Breeding for Nut Production in the Eastern United States - Revord, Ronald S.; Miller, Gregory; Meier, Nicholas A.; Webber, John Bryan; Romero-Severson, Jeanne; Gold, Michael A.; Lovell, Sarah T. (Frontiers in Plant Science, 2022)
Chestnut cultivation for nut production is increasing in the eastern half of the US. Chinese chestnuts (Castanea mollissima), or Chinese hybrids with European (C. sativa) and Japanese chestnuts (C. crenata), are cultivated due to their high kernel quality, climatic adaptation, and disease resistance. Several hundred thousand pounds of high-quality fresh nuts are taken to market every fall, and several hundred additional orchards are entering bearing years. Grower-led on-farm improvement has largely facilitated this growth. A lack of significant investments in chestnut breeding in the region, paired with issues of graft incompatibility, has led many growers to cultivate seedlings of cultivars rather than grafted cultivars. After decades of evaluation, selection, and sharing of plant materials, growers have reached a threshold of improvement where commercial seedling orchards can be reliably established by planting offspring from elite selected parents. Growers recognize that if cooperation persists and university expertise and resources are enlisted, improvement can continue and accelerate. To this end, the University of Missouri Center for Agroforestry (UMCA) and chestnut growers throughout the eastern US are partnering to formalize a participatory breeding program – the Chestnut Improvement Network. This partnership entails the UMCA providing an organizational structure and leadership to coordinate on-farm improvement, implement strategic crossing schemes, and integrate genetic tools. Chestnut growers offer structural capacity by cultivating seedling production orchards that provide financial support for the grower but also house segregating populations with improved individuals, create in situ repositories, and selection trials, creating great value for the industry.